Does Regional Affliation Inﬂuence Employees’ Perception of Tourism Policy in Cultural Tourism? - Vučetić, Aleksa; Ateljević, Jovo; Pivac, Tatjana; Kovačević Pejaković, Sanela (Turizam, 2018)
Te study tries to explain the inﬂuence of regional afliation on employees’ perception of tourism policy in the sector of cultural tourism. Te main aim is to explore whether there is a difference between regional afliations of employees and employees’ perception of tourism policy in the sector of cultural tourism in Montenegro. Te survey was conducted using the interviewing, and the main statistical procedures were factor analysis and multivariate analysis of variance. Research outcome is a signifcant diﬀerence between employees in the northern and the coastal region of Montenegro, in the employees’ perception of the importance of measures and activities of tourism policy in the sector of cultural tourism. However, that diﬀerence could not signifcantly inﬂuence tourism policymaking process and the quality of specifc tourism policy, which is intended for development of cultural tourism in Montenegro. Most of the signifcant diﬀerences depend on measures and activities, which do not directly inﬂuence the growth and development of cultural tourism that way. Te study is inspired by the Erasmus+ CULTURWB project.